Low-dose doxycycline inhibits hydrogen peroxide-induced oxidative stress, MMP-2 up-regulation and contractile dysfunction in human saphenous vein grafts - Saeed M; Arun MZ; Guzeloglu M; Onursal C; Gokce G; Korkmaz CG; Reel B (Dove Medical Press, 2019)
Mazen Saeed,1 Mehmet Zuhuri Arun,2 Mehmet Guzeloglu,3 Ceylan Onursal,1 Goksel Gokce,2 Ceren Gonen Korkmaz,2 Buket Reel21Ege University, Faculty of Pharmacy, Department of Pharmacology, 35100 Bornova, Izmir, Turkey; 2Ege University, Faculty of Pharmacy, Department of Clinical Pharmacy, 35100 Bornova, Izmir, Turkey; 3Optimed Hospital, Department of Cardiovascular Surgery, 59500 Corlu, Tekirdag, TurkeyBackground: Cardiopulmonary bypass (CPB) applied during coronary artery bypass grafting (CABG), promotes inflammation, generation of reactive oxygen species (ROS) and up-regulation of matrix metalloproteinases (MMPs). All these complications may lead to contractile dysfunction, restenosis and early graft failure, restricting long-term efficacy of bypass grafts. Low-dose doxycycline is a potent MMP inhibitor and ROS scavenger. In this study, we aimed to investigate the effects of doxycycline on ROS generation, MMP regulation and contractile dysfunction induced by H2O2 in human saphenous vein (HSV) grafts.Methods: HSV grafts (n=7) were divided into four groups after removing endothelial layer by mechanical scratching and incubated with 10 μM H2O2 and/or 10 μM doxycycline for 16 hrs. Untreated segments served as control. Concentration–response curves to noradrenaline (NA), potassium chloride (KCl), serotonin (5-HT) and papaverine were performed. Superoxide anion and other ROS levels were determined by using lucigenin- and luminol-enhanced chemiluminescence assays, respectively. Expression/activity of gelatinases (MMP-2/MMP-9) was examined by gelatin zymography. MMP-13 expression was evaluated by immunostaining/immunoscoring.Results: H2O2 incubation increased superoxide anion and other ROS levels. Doxycycline prevented these increments. H2O2 suppressed contractile responses to NA, KCl and 5-HT. Doxycycline ameliorated contractions to NA and KCl but not to 5-HT. H2O2 or doxycycline did not altered relaxation to papaverine. MMP-2 and MMP-13 expression increased with H2O2, but doxycycline inhibited MMP-2 up-regulation/activation.Conclusion: Low-dose doxycycline may have beneficial effects on increased oxidative stress, MMP up-regulation/activation and contractile dysfunction in HSV grafts.Keywords: hydrogen peroxide, doxycycline, oxidative stress, matrix metalloproteinase, human saphenous vein